1998
DOI: 10.1007/s002130050621
|View full text |Cite
|
Sign up to set email alerts
|

Kappa opioid-mediated behavioral sensitization in the preweanling rat: relationship to Fos immunoreactivity

Abstract: When given acutely, drugs that stimulate kappa opioid receptors (e.g., U-50,488) enhance the locomotor activity of preweanling rats and induce regional increases in Fos immunoreactivity (IR). In contrast, the effects of chronic treatment with kappa opioid agonists are unknown. The purpose of the present study was two-fold: first, to determine whether repeated treatment with a kappa opioid agonist would sensitize the locomotor activity of preweanling rats and, second, to determine whether changes in Fos IR corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
1
4
1
Order By: Relevance
“…Moreover, we observed that this effect lasts for at least eight days in the infant rat (Castello et al, 2016), which also contrasts with the literature employing different psychostimulants, showing that sensitization acquired during the second postnatal week of life does not last for more than three days (McDougall et al, 1994, Collins et al, 1998, McDougall et al, 1999. Considering the long-term persistence of tolerance and sensitization, the present results also have relevance for the ethanol literature.…”
Section: Please Insert Figure 2b Herecontrasting
confidence: 99%
“…Moreover, we observed that this effect lasts for at least eight days in the infant rat (Castello et al, 2016), which also contrasts with the literature employing different psychostimulants, showing that sensitization acquired during the second postnatal week of life does not last for more than three days (McDougall et al, 1994, Collins et al, 1998, McDougall et al, 1999. Considering the long-term persistence of tolerance and sensitization, the present results also have relevance for the ethanol literature.…”
Section: Please Insert Figure 2b Herecontrasting
confidence: 99%
“…It is speculated that different KOR populations, located in different brain regions, may mediate U-50,488 effects (Charntikov et al, 2008; Kuzmin et al, 2000). This notion is intriguing because U-50,488 induces hyperactivity in developing rats, while inducing hypoactivity in adult rats (Collins et al, 1998; McDougall et al, 1997), yet it attenuates drug reward in developing and adult rats in a similar manner (Bolaños et al, 1996; Crawford et al, 1995). …”
Section: Discussionmentioning
confidence: 99%
“…The purpose of Experiment 2 was to determine whether pretreating rats with a compound other than cocaine would differentially affect the expression of context-specific and context-independent behavioral sensitization. MK-801 (an NMDA antagonist), U50,488 (a kappa opioid agonist), and methylphenidate (a psychostimulant) were used because all three drugs typically induce substantial locomotor activity in preweanling rats (Duke, Meier, et al, 1997; Frantz & Van Hartesveldt, 1999; Jackson & Kitchen, 1989; McDougall, Collins, Karper, Watson, & Crawford, 1999) and are capable of inducing a sensitized locomotor response (Collins, Zavala, Ingersoll, Duke, Crawford, & McDougall, 1998; Duke, O'Neal, & McDougall, 1997; McDougall et al, 1999). On PD 19, rats were pretreated with MK-801, U50,488, methylphenidate, or cocaine before placement in activity chambers or small, enclosed anesthesia chambers.…”
Section: Methodsmentioning
confidence: 99%